2010
DOI: 10.1152/japplphysiol.00797.2009
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent vs. central motor effects of ethanol on breathing

Abstract: Ethanol, one of the most widely used drugs in Western society, worsens obstructive sleep apnea in humans. No studies, however, have distinguished between two primary mechanisms that could mediate suppression of genioglossus (GG) activity with ethanol. We test the hypothesis that ethanol suppresses GG activity by effects at the hypoglossal motor pool and/or by state-dependent regulation of motor activity via independent influences on sleep/arousal processes. Intraperitoneal injections of ethanol (1.25 g/kg, n ϭ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 60 publications
(133 reference statements)
0
14
3
Order By: Relevance
“…In addition to producing these markers of sleep-promotion/reduced arousal, ethanol also caused a state-dependent decrease in GG activity, but did not affect diaphragm activity or respiratory rate across any sleep-wake state (Fig. 12) (582). The pattern of this state-dependent decrease in GG activity after ethanol was also similar to that produced in the nonrespiratory, postural (neck) muscle by ethanol (Fig.…”
Section: Integrative Physiology: State-dependent Versus Central Motormentioning
confidence: 60%
See 3 more Smart Citations
“…In addition to producing these markers of sleep-promotion/reduced arousal, ethanol also caused a state-dependent decrease in GG activity, but did not affect diaphragm activity or respiratory rate across any sleep-wake state (Fig. 12) (582). The pattern of this state-dependent decrease in GG activity after ethanol was also similar to that produced in the nonrespiratory, postural (neck) muscle by ethanol (Fig.…”
Section: Integrative Physiology: State-dependent Versus Central Motormentioning
confidence: 60%
“…Importantly, despite these state-dependent effects of ethanol on GG motor activity following systemic administration, local application of ethanol directly to the hypoglossal motor pool caused no change in GG activity compared to the time-control (sham) experiments with delivery of vehicle control (582). Overall, therefore, these data show that ethanol at physiologically relevant concentrations promotes sleep and alters electroencephalogram and postural motor activities indicative of a sedating effect.…”
Section: Integrative Physiology: State-dependent Versus Central Motormentioning
confidence: 64%
See 2 more Smart Citations
“…Data from the placebo session in these participants have been reported in a recent publication (Avraam et al, 2021) (Nicholas et al, 2010;Vecchio et al, 2010;Wilkinson et al, 2008Wilkinson et al, , 2010Woods et al, 2015). Transition of units between IP and IT units is common (Nicholas et al, 2010;Wilkinson et al, 2010), and likewise conversion of EP/ET to TT and vice versa have been observed (Nicholas et al, 2010).…”
Section: Participantsmentioning
confidence: 83%